2009
DOI: 10.1093/humrep/dep001
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells from pregnant women show higher proliferation rate unrelated to estrogen

Abstract: Despite the higher proliferation rate in pregnant women, ASCs showed consistency in cell differentiation capacity and were unaffected by donor status. This suggests that factors other than estrogen are responsible for the difference in proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
1
24
2
Order By: Relevance
“…According to their findings, whereas male ADSCs isolated from superficial adipose layer have greater osteogenic capacity than deep layer cells, no significant difference was observed between the cultures isolated from female donors. In contrast to our and previous results, Ng et al (2009) found that both donor reproductive status (pregnancy, premenopause and postmenopause) and in vitro E 2 treatment have no significant effect on proliferation rate of human ADSCs. Overall, these conflicting findings may reflect the fact that proliferation rate and differentiation potential of stem cells including ADSCs can be influenced by several factors, such as donor age, gender, cell isolation and culture techniques, tissue sources.…”
Section: Discussioncontrasting
confidence: 99%
“…According to their findings, whereas male ADSCs isolated from superficial adipose layer have greater osteogenic capacity than deep layer cells, no significant difference was observed between the cultures isolated from female donors. In contrast to our and previous results, Ng et al (2009) found that both donor reproductive status (pregnancy, premenopause and postmenopause) and in vitro E 2 treatment have no significant effect on proliferation rate of human ADSCs. Overall, these conflicting findings may reflect the fact that proliferation rate and differentiation potential of stem cells including ADSCs can be influenced by several factors, such as donor age, gender, cell isolation and culture techniques, tissue sources.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we hypothesize that the main effects of estrogen in improving ASC proliferation, migration and adipogenesis is mediated by ERα. In contrast to this, it was published that estrogen level variation can hardly alter the capacity for stem cell proliferation [36]. Differences between results of Ng et al and ours might result because different concentrations of estrogen were used for ASC-based experiments [36].…”
Section: Discussioncontrasting
confidence: 57%
“…Manotaya et al (2002) indicated that hematopoietic stem cell number and activity increased during pregnancy. In addition, Ng et al (2009) found that the proliferation rate of ADSCs from pregnant women was higher than ADSCs isolated from preand postmenopausal women. We also detected the effect of progesterone and estradiol on rADSC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen receptor is the decisive factor influencing cellular response to estrogen (Cobellis et al, 2002), and it was shown to exist in MSCs (Zhou et al, 2001;Wang et al, 2006). Ng et al (2009) showed that upon binding estrogen receptors on the cell surface, estrogen activated specific genes and eventually affected cellular processes. However, no differences in proliferation rates were observed when ADSCs from pregnant, premenopausal or menopausal women were treated with exogenous estrogen.…”
Section: Discussionmentioning
confidence: 99%